2016
DOI: 10.1111/asj.12656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forsythia suspensa extract and chito‐oligosaccharide alone or in combination on performance, intestinal barrier function, antioxidant capacity and immune characteristics of weaned piglets

Abstract: We investigated the effects of Forsythia suspensa extract (FSE) and chito-oligosaccharide (COS), alone or together, on performance and health status of weaned piglets. The treatments included a basal diet and three diets with 160 mg/kg COS, 100 mg/kg FSE, or 100 mg/kg FSE and 160 mg/kg COS. Supplementation with COS or FSE alone improved (P < 0.01) average daily gain and feed conversion ratio compared with the basal diet in the first 2 weeks. On day 14, COS or FSE supplementation separately produced stronger (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 42 publications
9
31
0
Order By: Relevance
“…In our study, pigs fed the diet containing CHE had greater ATTD of DM on day 28 of the experiment compared with pigs fed control diets, which was in agreement with Zhao et al (2017), who demonstrated that dietary F. suspensa extract supplementation increased the ATTD of DM in weaned pigs on day 14 and day 28 of the experimental. The increased concentrations of immune markers in serum and faecal SCFAs in weaned pigs consumed CHE in our study may explain the positive effects of CHE supplementation on diarrhoea frequency and nutrient digestibility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, pigs fed the diet containing CHE had greater ATTD of DM on day 28 of the experiment compared with pigs fed control diets, which was in agreement with Zhao et al (2017), who demonstrated that dietary F. suspensa extract supplementation increased the ATTD of DM in weaned pigs on day 14 and day 28 of the experimental. The increased concentrations of immune markers in serum and faecal SCFAs in weaned pigs consumed CHE in our study may explain the positive effects of CHE supplementation on diarrhoea frequency and nutrient digestibility.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Huang et al (2012) observed this phenomenon and explained this by suppressed E. coli growth in the gut. In addition, Zhao et al (2017) reported significantly increased immune function when weaned pigs were fed diets containing 100 mg/kg Forsythia suspensa extract.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al [ 127 ] found that the anti-aging effect of phillyrin ( 60 ) is closely related to the antioxidant effect in aging model mice. Interestingly, the Forsythia Fructus extract has been used as an animal feed additive in weaned piglets and Arbor Acre broilers, mainly due to the improvement in growth performance via the modulation of some endogenous antioxidant molecules and oxidative stress biomarkers (SOD, GSH-Px and MDA) [ 128 , 129 , 130 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…Weaning stress decrease growth performance and damage the immune function of piglets [1,2,17]. Supplementation of plant extracts improve growth performance, alleviate oxidant stress and improve immune function, thereby reduce the negative effects of weaning stress on piglets [18,19]. LE exhibits antioxidant function [12][13][14] and immunomodulatory function on RAW264.7 cells and mice [11,[20][21][22], thus is a potential potential alternatives protection against early weaned stress in piglets.…”
Section: Discussionmentioning
confidence: 99%